Contextualizing Justice in Times of Crisis: A Study of QS. Al-Mā’idah 5:38 and its Application in Criminal Theft Cases - Pangastuti, Berlian Puji (UIN Sunan Kalijaga Yogyakarta, 2023)
The Qur'an is considered a guide for all of humanity, offering valuable insights and guidance that is adaptable to changing circumstances and the challenges of modern life. This paper focuses on the issue of theft in times of emergency, which is an issue of concern for many societies today. In particular, the paper examines the Quranic verse, QS Al-Mā’idah 5:38, which states that men and women who steal are punished by having their hands cut off. The paper employs Abdullah Saeed's interpretation method, which emphasizes the importance of contextualizing Quranic verses in response to contemporary realities. The findings of the study indicate that the verse in question has a universal value in terms of justice, as it seeks to ensure that people's basic rights are protected and fulfilled in order to prevent theft. However, if basic needs are not met and a person is forced to steal in order to survive, it may be permissible to do so, as long as the limits of necessity are not exceeded. The verse also has a temporal nature, as the law of cutting hands can be replaced with alternative punishments, depending on the circumstances. In the Islamic context, this alternative might be ta'zir, while in the Indonesian context, it might involve a restorative justice process. Overall, the paper offers valuable insights into how the Qur'an can be interpreted to address the challenges of modern life, especially in times of emergency. The study highlights the importance of contextualizing Quranic verses in order to respond effectively to changing circumstances, while still upholding the core values of justice and compassion.